“Circumstantially Volatile”: A narrative study of the lived first-year experience at a New England liberal arts college - Patrick Flynn (Adult Education Research Conference, 2020)
College-ready, traditional-aged undergraduate students in the United States have been stopping out at an increasingly higher rate over the last forty years. Many students stop out after the first year, which has led researchers to focus on the first-year experience (FYE) as a way of understanding the trend. While the FYE literature, complemented by research in gender theory, the college transition, emerging adulthood, and college student development provide a foundation for considering the problem, there have been very few studies concerning the FYE of white males. Understanding the FYE at a substantive level for this population will lead to further research and hopefully open pathways to increasing retention. The study at the center of this paper addressed the research question, “How do college-ready, traditional-aged male students experience the first year of postsecondary education at a small liberal arts college in Maine?” Over the course of nine months, from September 2017 to May 2018, participants responded to over forty researcher-generated text messages and engaged in three semi-structured qualitative interviews and one brief survey. Data were collected, organized through NVivo, and then expressed in narrative form. Analysis was conducted using grounded theory and case study. One participant withdrew from the college; another participant struggled significantly but persisted; and three other participants developed throughout the FYE and entered their second year confident in their ability to succeed. The study suggests that students in transition to college are more likely to persist beyond the first year if they 1) exhibit social resilience; 2) possess a capacity for self-reflection; 3) demonstrate a willingness to reset priorities; and 4) set a tangible goal that extends beyond the first year.
Keywords: first-year experience; college transition; college student development; emerging adulthood; gender; narrative; grounded theory; case study